PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENGELUARAN PEMERINTAH DI INDONESIA TAHUN 2014-2018 - Sari Weni Berutu; Khairil Anwar (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study aims to determine the effect of local taxes and levies on Government expenditures in Indonesia in 2014-2018. The data used in this study is panel data from 2014 to 2018. The method used is panel data regression analysis. The results of the study partially show that local taxes have a positive and significant effect on Government expenditures in Indonesia in 2014-2018, and local fees do not have a significant effect on government expenditures in Indonesia in 2014-2018. Simultaneously, local taxes and levies have a positive and significant effect on government expenditures in Indonesia in 2014-2018.Keywords: Local Taxes, Regional Retributions, Government Expenditures